Screening of Novel Cry Genes Active Against Nematodes from Bacillus thuringiensis Thai Isolates - Meirizka, RE; Budiharjo, A; Pujiyanto, S (Bioma : Berkala Ilmiah Biologi, 2020)
Cry proteins of Bacillus thuringiensis have been successfully used as biopesticides and transgenic crops throughout the world. However, resources against the most serious agricultural pathogens, plant root-knot nematodes, are limited. Nematicidal Cry proteins produced by Bacillus thuringiensis (Bt) are used for effiecient pest control. Cry 5, Cry 6, Cry 21, and Cry 55 were known to have nematicidal activity. In the present study, 80 Bt isolates from diverse locations in Thailand have been investigated for their nemeticidal cry gene content. Bt isolates were screened through Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE), Polymerase Chain Reaction (PCR), ligated into the cloning vector PJET 1.2/blunt, transformed into Escherichia coli DH5É‘, and diagnostic restriction enzyme digest for the presence of nematode-active cry genes. Of 80 Bt Thai isolates, 24 isolates (30%) have 54-kDa protein which is similar with the molecular weight of Cry 6 protein and 5 isolates (6%) have Â±45 kDa protein which is similar with the molecular weight of Cry 55protein. Only one Bt isolate (Bt 32) was suspected to be positive for the presence of cry 6 gene.